Nanobiocatalysts for biodiesel synthesis through transesterification—a review - Najeeb, Jawayria; Akram, Sadia; Mumtaz, Muhammad Waseem; Muhammad Danish; Ahmad Irfan; Touqeer, Tooba; Rashid, Umer; Wan Ab Karim Ghani, Wan Azlina; Shean, Thomas Yaw Choong (MDPI, 2021)
Converting useless feedstock into biodiesel by utilizing the process of transesterification has been regarded as an alternative approach recently used to address the fuel and energy resources shortage issues. Nanobiocatalysts (NBCs), containing the biological component of lipase enzyme immobilized on nanomaterials (NMs), have also been presented as an advanced catalyst to effectively carry out the process of transesterification with appreciable yields. This study highlights the fundamentals associated with NBCs and the transesterification reaction catalyzed by NBCs for summarizing present academic literature reported in this research domain in recent years. Classification of the NBCs with respect to the nature of NMs and immobilization methods of lipase enzyme is also provided for organizing the recently documented case studies. This review is designed to act as a guideline for the researchers aiming to explore this domain of biodiesel production via NBCs as well as for the scholars looking to expand on this field.